An Analysis of Teachers’ Competence in Applying Instructional Variations in IPAS Learning: A Study in Grade V of SDN 004 Domo, Kampar Regency - Haviz Dazaqy; Leny Julia Lingga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze teachers’ skills in applying variations in IPAS (Integrated Science and Social Studies) learning in Grade V of SDN 004 Domo, Kampar Regency, focusing on teaching style variations, the use of media, and teacher-student interaction patterns. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. Data were analyzed using Miles and Huberman’s interactive model, including data collection, reduction, display, and conclusion drawing. The findings reveal that teachers applied variations in teaching style, yet the use of media and interaction patterns remained limited. The study concludes that variations in teaching practices positively influenced student engagement, although they were not fully optimized across all aspects. The implication highlights the need for continuous professional development programs to enhance teachers’ creativity and consistency in implementing varied learning strategies in line with the demands of the Merdeka Curriculum.